Why Are Dithienylethene‐Linked Biscobaltocenes so Hard to Photoswitch?. Issue 6 (9th February 2017) - Escribano, Alejandra; Steenbock, Torben; Stork, Conrad; Herrmann, Carmen; Heck, Jürgen
Abstract: Attaching an organometallic unit to a dithienylethene (DTE) molecular switch can allow one to vary its switching and spectroscopic properties, and to create switchable magnetic properties. In this work, two different dithienylethene molecular switches are used as a bridge between two cobalt sandwich units. The only difference between the switching cores is in the size of the cycloalkene ring connecting both thiophene rings. The complexes present different oxidation states for the cobalt atoms, which are demonstrated to determine the switching reaction. The UV/Vis measurements show that while the Co(I) complexes undergo the switching reaction, the Co(II, III) complexes switch poorly. Kohn–Sham density functional theory calculations indicate diabatic ring‐closure mechanisms and a large number of excited states hindering the cyclization reaction and favoring the relaxation to the open form of the molecular switch. Abstract : You can lead a horse to water… : The introduction of a dithienylethene (DTE) linker as a molecular switch between two paramagnetic sandwich complexes is quite successful, in contrast to the switching process. An explanation is given by means of DFT calculations.